Are Brazilian cervids at risk of prion diseases? - Ribeiro Falcao, Caio Bruno; Nunes Freire Lima, Isabel Luiza de Melo; Barbanti Duarte, Jose Mauricio [UNESP]; Mendes de Oliveira, Joao Ricardo; Torres, Rodrigo Augusto; Wanderley, Artur Maia; Gomes da Cunha, Jose Eriton; Garcia, Jose Eduardo (Taylor & Francis Inc, 2017)
Prion diseases are neurodegenerative fatal disorders that affect human and non-human mammals. Chronic Wasting Disease (CWD) is a prion disease of cervids regarded as a public health problem in North America, and polymorphisms at specific codons in the PRNP gene are associated with this disease. To assess the potential CWD susceptibility of South American free-ranging deer, the presence of these polymorphisms was examined in Mazama gouazoubira, Ozotoceros bezoarticus and Blastocerus dichotomus. Despite the lack of CWD reports in Brazil, the examined codons (95, 96, 116, 132, 225, and 226) of the PRNP gene showed potential CWD susceptibility in Brazilian deer. Low abundancy of deer in Brazil possibly difficult both CWD proliferation and detection, however, CWD surveillance may not be neglected.
Keywords: Blastocerus; chronic wasting disease; Mazama; neotropical deer; Ozotocerus; PrP; prion